Aspek Yuridis dalam Pertanggungjawaban Hukum Profesi Dokter pada Perspektif Pelayanan Informed Consent Untuk Mewujudkan Perlindungan Hukum - Dwi Sandry Resky Dzulhizza; Darwis Anatami; Ramon Nofrial (Jurnal Kajian Ilmiah, 2023)
The purpose of this study is to determine the regulation of obligations, the implementation of doctors, as well as to find out the constraints and solutions to the implementation of doctors' obligations to informed consent in medical practice to realize legal protection for patients. This research is normative juridical and supported by sociological / empirical research This research is normative and empirical juridical. Normative juridical research refers to laws and regulations, while empirical research is obtained in the field. The results of the study that the regulation regarding the approval of medical actions originated from the relationship between doctors and patients. The implementation of doctors' obligations to informed consent at Dentic Clinic is known that the provision of information in the form of informed consent began to be pursued earlier, but these efforts have not been carried out optimally. This is influenced by the large number of patients so that it is felt that it is necessary to take action quickly and it is considered that the patient has understood what is conveyed by the doctor, the information submitted by the health worker is not understood by the patient, the provision of information to ask for a signature on the consent sheet is sometimes done by the nurse even though it is the authority of the doctor, the patient is often not given the opportunity to re-read the form given, so that patients feel that they have never been given information before medical treatment, as well as inadequate Human Resources.